As decisões interpretativas proferidas pelo Supremo Tribunal Federal no controle abstrato de constitucionalidade - Colnago, Cláudio Oliveira Santos (2006)
This dissertation deals with the limits and criteria established by the Brazilian Supremo Tribunal Federal when this Court uses the interpretative forms of decision, as the decisions taken by the judicial review that maintain the statute’s text and change only their meaning. The inductive method was applied in the solution of the problem, also applying the documental and bibliographic research techniques. The base theory chosen consists on the writings of Hector López Bofill and Francisco Javier Díaz Revorio. These authors were chosen due to their complete analysis of the foreign experience with the interpretative forms of decision. Therefore, a comparative study about the Supremo Tribunal Federal’s decisions was implemented, with the goal of identifying the Court’s tendencies. Based on the careful analysis of the decisions selected, we were able to determine that there is a great tendency in the Court on unifying the interpretation of the legal statutes, justifying this tendency with the need of adapting it under the Constitution’s Supremacy, which can generate the problem of the immobilization of interpretation of the statute. This situation generated the understanding by which the Court should adopt more frequently interpretative forms of decision which exclude the unconstitutional meanings, without the desire of establishing the “only meaning constitutionally compatible”. We could verify that the STF can change it’s interpretation established in a interpretative form of decision, since it hasn’t in the first decision expressly excluded an the meaning which is being used in the second one. There must be also some changes fact or law changes to justify the new interpretation. We could also conclude that the article 97 of Brazilian Constitution doesn’t apply to the interpretative forms of decision, since these already prevent the institutional tension which the article seeks to avoid. It was verified also that the interpretative forms of decision are justified by the need of harmony between the Executive, the Legislative and the Judiciary, and also by the search for institutional stability necessary for the right functioning of the rule of Law. We could also infer that the Court considers itself competent to take interpretative forms of decision about any kind of statute (including Amendments to the Constitution), and it is also limited by the idea of Separation of Powers, meaning a deep respect of the Legislators will, considered on the subjective aspect.